Assessment of the Biological Activities of Calendula officials Extracts - Ibrahim, hiba; Shubrem, alaa; mohammed, Wasnaa (Iraqi National Journal of Nursing Specialties, 2013)
Objective: To assess two kinds of extraction (aqueous and methanolic) for Calendula officials using flowers, leaves and stems and studying their antibacterial activity against five different bacteria. Methodology: Calendula officials were selected to carry out this study. Flowers, leaves and stems were collected from local markets in Baghdad then dried in shade for 7 days and grinded to fine powder. Aqueous hot extracts for 2hr. at (100c˚) and alcoholic extracts for 48 hrs at (80c˚) were performed using flowers, leaves and stems then studied antibacterial effect against five different bacterial genuses by using well diffusion technique. Results: This study showed that hot aqueous extracts for 2hr. to all parts of Calendula officials indicated no antibacterial activity. While, methanolic extracts of flowers, leaves and stems for 48hrs had antibacterial activity and the highest values for inhibition zone shown in staphylococcus aureus and Escherichia coli. Recommendations: The present study has been suggested to use Calendula officials flowers extract as alternative medical therapy for microorganisms which may resist conventional treatment. This study is a first step for another future studies. It is necessary to use various extraction methods to give active materials with high percentage, although different organic solvents to be used with Calendula officials plant to obtain extracts used for testing different kinds of microorganisms which have highly resistance to conventional treatment.